Augmented Reality Katalog Penjualan IT Hardware Pada PT. Unibless Menggunakan Algoritma MSER (Maximally Stable Extermal Regions) - Fahri al Rasyid; Iskandar Fitri; Andrianingsih Andrianingsih (SMATIKA JURNAL, 2020)
In today's digital age, based on a lot of business competition to attract consumers who still use promotions through brochures or websites, then with the advent of Augmented Reality (AR) technology, business entrepreneurs especially in the field of IT Hardware can adopt AR technology in the marketing of its products. The technology can display 3-dimensional objects in real time, so consumers can see hardware IT models more interactively and interestingly. In supporting AR development, the study used the MSER (Maximally Stable Extremal Regions) algorithm identified as one of the best image capturers due to its resistance to changes in angle of view, scale or pixel, and lighting, as well as sensitivity to blurred imagery by testing based on pixel density by intensity, in terms of accuracy of light reusability rate, as well as the speed at which 3D objects appear based on distance when reading markers. Thus the researchers get the appropriate test results that the tighter the pixels then the more perfect the AR object will appear, and also with sufficient light intensity and suitable distance, the easier it will be to appear perfect. The results of this study resulted in an application that runs on the android platform as one of the supporting in the marketing promotion of IT Hardware products in a more interactive way, because the use of AR with MSER algorithm is very helpful for the company to more clearly provide in detail and detail regarding the 3D object specifications of a product that wants to be sold without carrying the product, and can also help consumers to see products marketed by other sellers or companies so that consumers will be interested in buying IT Hardware products from PT. Unibless.